1999
DOI: 10.1007/s004140050258
|View full text |Cite
|
Sign up to set email alerts
|

Perimortem fixation of the gastric and duodenal mucosa: a diagnostic indication for oral poisoning

Abstract: Two cases of fatal oral poisoning are presented. In the first case, a 40-year-old man died due to a lethal dose of mercury (blood concentration 113.8 microg/ml) and in the second, a 34-year-old man died of chloralhydrate overdose with a lethal blood concentration of trichloroethanol (52 microg/ml), the active metabolite of chloralhydrate. In both cases gross examination and histology showed an unusually well preserved gastrointestinal mucosa in addition to unspecific signs of intoxication. The two cases demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…The recognition of chumbinho inside the stomach was crucial to its research and confirmation in the toxicology test as the cause of death from acute poisoning. The examination of the gastric mucosa in oral poisonings can reveal bleeding, swelling, and color changes as well as histological findings that can assist the medical legal study [15].…”
Section: Resultsmentioning
confidence: 99%
“…The recognition of chumbinho inside the stomach was crucial to its research and confirmation in the toxicology test as the cause of death from acute poisoning. The examination of the gastric mucosa in oral poisonings can reveal bleeding, swelling, and color changes as well as histological findings that can assist the medical legal study [15].…”
Section: Resultsmentioning
confidence: 99%
“…This contact methanol tissue could have had a corrosive effect on the non-fixed deep mucosa which could be responsible for the coagulative necrosis as we have not found vascular damage or thrombosis or other signs of tissue ischaemia. Tsokos et al [10] reported two cases of perimortem fixation of the gastric mucosa due to lethal doses of mercury and chloral hydrate, two oral toxics with fixative effects. In both cases, gastric mucosa was preserved, unaffected by autolysis with an intact epithelial layer, findings very similar to those seen in our own case.…”
Section: Discussionmentioning
confidence: 98%
“…The "fixing" of the stomach by formaldehyde may produce delayed absorption following formalin ingestion. 11 Formaldehyde is a corrosive material that can produce late sequelae similar to the more common ingestion of acids and alkali. 12 Most of the formalin poisonings reported were suicidal in nature.…”
Section: Discussionmentioning
confidence: 99%